Perbandingan Kelayakan Usahatani Padi Semi Organik Dan Non Organik: Studi Kasus Pada Kelompok Tani Taruna Tani Muara Hurip Di Kelurahan Cikalang Kecamatan Tawang Kota Tasikmalaya (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2023)
Rice is included in the class of annual crops or young plants, namely plants that are usually short-live less than one year and only one time to produce, after the planting period ends the plant will die or be replaced by a new plant. Rice plants have a stems that are branched, the leng of stem depends on the type. Local types of rice have longer stems than superior types of rice. Rice stem segments are hollow and round, as with other plants, the roots of the rice both taproot and fibrous roots are branched. In the agricultural cultivation system requires technology to facilitate farming activites. One of the farmer groups that cultivate semi-organic and non-organic rice is the Muara Hurip Taruna Tani Farmer Groups. This reaserch aims to determine the cost, revenue, and comparison of the feasibility of semi-organic and non-organic rice farming. The results showed that the total cost incurred by semi-organic rice farmers was Rp. 3.282.823,73 while the total cost for non-organic rice farmers was Rp. 4.792.901,73. Total revenue for semi-organic rice farmers amounted Rp. 20.400.000,00, while for non-organic rice farmers revenue amounted Rp. 13.200.000,00. R/C ratio of semi-organic rice farming is greater at 6,21, meaning that every one Rupiah of capital spent obtained revenue Rp. 6,21. While the value of the R/C ratio of non-organic rice farmers is 2,75, meaning that every one Rupiah of capital spent obtained revenur Rp.2,75. This shows that for both farms is feasible to cultivate.